PENGATURAN KECEPATAN MOTOR AC SEBAGAI AERATOR UNTUK BUDIDAYA TAMBAK UDANG DENGAN MENGGUNAKAN SOLAR CELL - Sofiah Sofiah; yosi apriani (Universitas PGRI Palembang, 2019)
Abstract—— Aerator is a tool to help shrimp farmers to drain air or increase the value of oxygen so that more oxygen will enter the water to help grow the shrimp. Aerator consists of several supporting components namely AC motor, accumulator, inverter, impeller and frame. This aerator is designed using solar cells as an energy source. In the results of testing the solar cell supplying 5.7 amperes of current with a voltage of 17.5 volts, the accumulator works on a voltage of 12v / 70Ah, with charging current from the solar cell and accumulator charger 5.7 amperes with a charging time of approximately 12.2 hours, maximum calculated inverter power is 500 watts